An Essay of Self-criticism of the Russian Intelligencija: Language, Literature, History (ENTHYMEMA, 2018)
Review of the book: Klimova, S.M. Intelligencija v poiskach identichnosti: Dostoevsky – Tolstoy. SAleteja, 2018.
Keywords: Intelligencija; Dostoevsky; Lev Tolstoy; Strachov; the Russian idea; philosophy of life